Morphometric characterization of Khaya senegalensis in southern Minas Gerais State, Brazil - Reis, Luciano Helvécio Villela; Rocha, Lucas Fernandes [UNESP]; dos Santos, Juscelina Arcanjo; de Souza, Cléber Rodrigo; Trazzi, Paulo André; Barbosa, Lorena Oliveira; de Carvalho, Dulcinéia (Instituto de Pesquisa e Estudos Florestais (IPEF), 2021)
Understanding the morphometry patterns of planted trees is an essential forestry methodology to develop accurate silvicultural practices. The genus Khaya comprises several economically important tree species due to its high quality of the wood and it has been broadly implemented in economical plantations. Here, we analyzed the morphometric characteristics of Khaya senegalensis (Desv.) A. Juss. from 484 trees in a 4 years-old plantation located in Southern Minas Gerais state, Brazil. Therefore, we measured the diameter at breast height (DBH), total height (TH), and crown insertion height (CIH). Using those variables, we estimated the crown length (CL), the slenderness ratio (SR), and the crown proportion (CP). The crown quality (CQ) and stem quality (SQ) were estimated by visual grading. We then performed regression models for all morphometric variables to analyze the distribution of each one. The survival analysis and mean annual increment at 4 years of age (48 months) were calculated. We used the Spurr model to estimate the population volume. The SR and CL variables showed high levels of variation. Most morphometric variables, except for SC, presented a significant correlation with DBH. The SQ and CQ presented a linear relationship with the size of the tree. As expected, tree diameter increased with the best quality of crowns and stems. We found a low morphometric relationship between TH and DBH. On the other hand, a linear trend was found with the increase of DBH, CL, and CP. The percentage of survival and the mean annual increment at 4 years of age were 97.2% and 3.31 m3/ha/year, respectively. The characterization revealed a good adaptation of the species within the plantation area in Southern Minas Gerais State. However, further and periodical analysis should create a robust database and make more assertive inferences of the morphometric variables.
Caracterização morfométrica de Khaya senegalensis no sul de Minas Gerais, Brasil
Keywords: African mahogany; Alternative species; Silvicultural characteristics